Case of nivolumab-induced sclerosing cholangitis: lessons from long-term follow-up. Issue 1 (10th September 2020) - McClure, Tess; Cui, Wanyuan; Asadi, Khashayar; John, Thomas; Testro, Adam
Abstract : Nivolumab is an immune checkpoint inhibitor used to treat multiple solid-organ malignancies. While many of its immune-related adverse events are well established, nivolumab-induced sclerosing cholangitis remains poorly characterised, with no defined diagnostic criteria. Moreover, data regarding long-term outcomes are particularly lacking. We present a biopsy-proven case of nivolumab-induced sclerosing cholangitis, which uniquely captures 18 months of follow-up post-treatment. Our case highlights key features of intrahepatic subtype sclerosing cholangitis and suggests durable response to corticosteroid therapy.